SLCO1B1 genetic polymorphism influences mycophenolic acid tolerance in renal transplant recipients. (December 2010) - Michelon, Hugues; König, Jörg; Durrbach, Antoine; Quteineh, Lina; Verstuyft, Céline; Furlan, Valérie; Ferlicot, Sophie; Letierce, Alexia; Charpentier, Bernard; Fromm, Martin F; Becquemont, Laurent
Aims: This study aimed to determine the influence of gene candidates on mycophenolic acid (MPA) response during the first year of renal transplantation.Materials & methods: A total of 218 renal transplant recipients who received MPA from the first day of transplantation at a fixed dose of 2 g/day were genotyped for ABCB1, ABCC2, UGT2B7, UGT1A9, SLCO1B1, SLCO1B3 and IMPDH1 polymorphisms. Clinical end points were MPA-related adverse drug reactions (ADRs) and acute rejection episodes during the first year post-transplantation.Results: After correction for multiple statistical testing, SLCO1B1 (encoding the hepatic uptake transporter OATP1B1) was the only gene associated with MPA-related ADRs, showing a 75% risk reduction in favor of a protective effect of the SLCO1B1*5 allele (p = 0.002). In vitro experiments showed that MPA metabolites MPA-phenyl-glucuronide and MPA-acyl-glucuronide are substrates of OATP1B1. Their transport was decreased in the presence of the variant transporter (OATP1B1*5).Conclusion: These results suggest for the first time that carriers of the SLCO1B1*5 allele seem to be protected from MPA-related ADRs.